Unraveling Electron Dynamics in p-type Indium Phosphide (100): A Time-Resolved Two-Photon Photoemission Study - Diederich, Jonathan; Velasquez Rojas, Jennifer; Zare Pour, Mohammad Amin; Ruiz Alvarado, Isaac Azahel; Paszuk, Agnieszka; Sciotto, Rachele; Höhn, Christian; Schwarzburg, Klaus; Ostheimer, David; Eichberger, Rainer; Schmidt, Wolf Gero; Hannappel, Thomas; et al. (Journal of the American Chemical Society)

Substrate Doping and Defect Influence on P-Rich InP(001):H Surface Properties - Sciotto, Rachele; Ruiz Alvarado, Isaac Azahel; Schmidt, Wolf Gero (Surfaces)
Density-functional theory calculations on P-rich InP(001):H surfaces are presented. Depending on temperature, pressure and substrate doping, hydrogen desorption or adsorption will occur and influence the surface electronic properties. For p-doped samples, the charge transition levels of the P dangling bond defects resulting from H desorption will lead to Fermi level pinning in the lower half of the band gap. This explains recent experimental data. For n-doped substrates, H-deficient surfaces are the ground-state structure. This will lead to Fermi level pinning below the bulk conduction band minimum. Surface defects resulting from the adsorption of additional hydrogen can be expected as well, but affect the surface electronic properties less than H desorption.

Atomic wires on substrates: Physics between one and two dimensions - Pfnür, H.; Tegenkamp, C.; Sanna, S.; Jeckelmann, E.; Horn-von Hoegen, M.; Bovensiepen, U.; Esser, N.; Schmidt, Wolf Gero; Dähne, M.; Wippermann, S.; Bechstedt, F.; Bode, M.; et al. (Surface Science Reports)

Defect-Assisted Exciton Transfer across the Tetracene-Si(111):H Interface - Krenz, Marvin; Gerstmann, Uwe; Schmidt, Wolf Gero (Physical Review Letters)

Time-bin entanglement in the deterministic generation of linear photonic cluster states - Bauch, David; Köcher, Nikolas; Heinisch, Nils; Schumacher, Stefan (APL Quantum)
We theoretically investigate strategies for the deterministic creation of trains of time-bin entangled photons using an individual quantum emitter described by a Λ-type electronic system. We explicitly demonstrate the theoretical generation of linear cluster states with substantial numbers of entangled photonic qubits in full microscopic numerical simulations. The underlying scheme is based on the manipulation of ground state coherences through precise optical driving. One important finding is that the most easily accessible quality metrics, the achievable rotation fidelities, fall short in assessing the actual quantum correlations of the emitted photons in the face of losses. To address this, we explicitly calculate stabilizer generator expectation values as a superior gauge for the quantum properties of the generated many-photon state. With widespread applicability in other emitter and excitation–emission schemes also, our work lays the conceptual foundations for an in-depth practical analysis of time-bin entanglement based on full numerical simulations with predictive capabilities for realistic systems and setups, including losses and imperfections. The specific results shown in the present work illustrate that with controlled minimization of losses and realistic system parameters for quantum-dot type systems, useful linear cluster states of significant lengths can be generated in the calculations, discussing the possibility of scalability for quantum information processing endeavors.

High-throughput antibody screening with high-quality factor nanophotonics and bioprinting

Schottky-barrier type infrared photodetector - Güsken, Nicholas Alexander

Plasmonic modulators: bringing a new light to silicon - Hoessbacher, C.; Baeuerle, B.; Del Medico, N.; De Leo, E.; Güsken, Nicholas Alexander; Heni, W.; Langenbach, A.; Tedaldi, V. (IET Conference Proceedings)

Electrifying the field of metasurface optics - Güsken, Nicholas Alexander; Brongersma, Mark L. (Photonics Insights)

Surface-near domain engineering in multi-domain x-cut lithium niobate tantalate mixed crystals - Bollmers, Laura; Babai-Hemati, Tobias; Koppitz, Boris; Eigner, Christof; Padberg, Laura; Rüsing, Michael; Eng, Lukas M.; Silberhorn, Christine (Applied Physics Letters)
Lithium niobate and lithium tantalate are among the most widespread materials for nonlinear, integrated photonics. Mixed crystals with arbitrary Nb–Ta ratios provide an additional degree of freedom to not only tune materials properties, such as the birefringence but also leverage the advantages of the singular compounds, for example, by combining the thermal stability of lithium tantalate with the larger nonlinear or piezoelectric constants of lithium niobate. Periodic poling allows to achieve phase-matching independent of waveguide geometry and is, therefore, one of the commonly used methods in integrated nonlinear optics. For mixed crystals, periodic poling has been challenging so far due to the lack of homogeneous, mono-domain crystals, which severely inhibit domain growth and nucleation. In this work, we investigate surface-near (<1μm depth) domain inversion on x-cut lithium niobate tantalate mixed crystals via electric field poling and lithographically structured electrodes. We find that naturally occurring head-to-head or tail-to-tail domain walls in the as-grown crystal inhibit domain inversion at a larger scale. However, periodic poling is possible if the gap size between the poling electrodes is of the same order of magnitude or smaller than the average size of naturally occurring domains. This work provides the basis for the nonlinear optical application of lithium niobate tantalate mixed crystals.

Charge transfer magnetoexcitons in magnetoabsorption spectra of asymmetric type-II double quantum wells - Röder, J.; Gerhard, M.; Fuchs, C.; Stolz, W.; Heimbrodt, W.; Koch, M.; Ngo, C.; Steiner, J. T.; Meier, Torsten (Physical Review B)

Optical imaging of ferroelectric domains in periodically poled lithium niobate using ferroelectric liquid crystals - Meier, Patrick A.; Keuker-Baumann, Susanne; Röder, Thorsten; Herrmann, Harald; Ricken, Raimund; Silberhorn, Christine; Kitzerow, Heinz-Siegfried (Opto-Electronics Review)
Ferroelectric liquid crystals exhibiting a chiral smectic C* phase are deposited on z cut periodically poled lithium niobate substrates and investigated by polarized optical microscopy. While the pure substrates placed between crossed polarizers and observed in transmission appear dark, uniformly aligned liquid crystal films deposited on these substrates show alternating domains with varying brightness. This effect can be attributed to the well-known coupling between the direction of the spontaneous polarization and the optical axis in the birefringent ferroelectric smectic C* phase. Quantitative measurements of the tilt angle between the local optical axis and the smectic layer normal confirm antiparallel orientations of spontaneous polarization of the liquid crystal from domain to domain, as expected by the periodic poling of the lithium niobate substrate. This effect provides a valuable non-destructive method of optical inspection of the quality of periodically poled ferroelectric substrates, which plays an important role in achieving quasi-phase-matching in non-linear optical applications.

Effects of Composition and Polymerization Conditions on the Electro-Optic Performance of Liquid Crystal–Polymer Composites Doped with Ferroelectric Nanoparticles - Nordendorf, Gaby; Jünnemann-Held, Gisela; Lorenz, Alexander; Kitzerow, Heinz-Siegfried (Nanomaterials)
The presence of a polymer network and/or the addition of ferroelectric nanoparticles to a nematic liquid crystal are found to lower transition temperatures and birefringence, which indicates reduced orientational order. In addition, the electro-optic switching voltage is considerably increased when a polymer network is formed by in situ polymerization in the nematic state. However, the resulting polymer network liquid crystal switches at similar voltages as the neat liquid crystal when polymerization is performed at an elevated temperature in the isotropic state. When nanoparticle dispersions are polymerized at an applied DC voltage, the transition temperatures and switching voltages are reduced, yet they are larger than those observed for polymer network liquid crystals without nanoparticles polymerized in the isotropic phase.

Influence of the Deposition Rate on the Alignment and Performance of Perylene-3,4,9,10-tetracarboxylic Tetraethyl Ester in an Organic Light Emitting Diode - Becker, David; Meier, Patrick; Kuhlmann, Andreas; Sternemann, Christian; Bock, Harald; Steinrück, Hans-Georg; Kitzerow, Heinz-Siegfried (ACS Applied Electronic Materials)

Investigation of nano-rods fabricated by the DNA origami method using static and dynamic light scattering - Zhang, Bingru; Martens, Kevin; Kneer, Luisa; Nguyen, Linh; Kempter, Susanne; Huber, Klaus; Kitzerow, Heinz-Siegfried (Molecular Crystals and Liquid Crystals)

Fifty years of liquid crystal research in the mirror of the German Liquid Crystal Conference - Giesselmann, Frank; Kitzerow, Heinz-Siegfried; Zentel, Rudolf (Liquid Crystals Today)

Bright Electrically Contacted Circular Bragg Grating Resonators with Deterministically Integrated Quantum Dots - Wijitpatima, Setthanat; Auler, Normen; Mudi, Priyabrata; Funk, Timon; Barua, Avijit; Shrestha, Binamra; Schall, Johannes; Limame, Imad; Rodt, Sven; Reuter, Dirk; Reitzenstein, Stephan (ACS Nano)

Low-temperature fabrication of amorphous carbon films as a universal template for remote epitaxy - Henksmeier, Tobias; Reuter, Dirk (Communications materials)

Polariton-Induced Transparency in Multiple Quantum Wells Probed by Time Domain Brillouin Scattering - Karzel, Marek; Samusev, Anton K.; Linnik, Tetiana L.; Littmann, Mario; Reuter, Dirk; Bayer, Manfred; Scherbakov, Alexey V.; Akimov, Andrey V. (ACS Photonics)

Floquet dynamics of ultracold atoms in optical lattices with a parametrically modulated trapping potential - Ali, Usman; Holthaus, Martin; Meier, Torsten (New Journal of Physics)
Abstract Experiments with ultracold atoms in optical lattices usually involve a weak parabolic trapping potential which merely serves to confine the atoms, but otherwise remains negligible. In contrast, we suggest a different class of experiments in which the presence of a stronger trap is an essential part of the set-up. Because the trap-modified on-site energies exhibit a slowly varying level spacing, similar to that of an anharmonic oscillator, an additional time-periodic trap modulation with judiciously chosen parameters creates nonlinear resonances which enable efficient Floquet engineering. We employ a Mathieu approximation for constructing the near-resonant Floquet states in an accurate manner and demonstrate the emergence of effective ground states from the resonant trap eigenstates. Moreover, we show that the population of the Floquet states is strongly affected by the phase of a sudden turn-on of the trap modulation, which leads to significantly modified and rich dynamics. As a guideline for further studies, we argue that the deliberate population of only the resonance-induced effective ground states will allow one to realize Floquet condensates which follow classical periodic orbits, thus providing challenging future perspectives for the investigation of the quantum–classical correspondence.